2009
DOI: 10.1080/00365520903194591
|View full text |Cite
|
Sign up to set email alerts
|

Propofol sedation for upper gastrointestinal endoscopy in patients with liver cirrhosis as an alternative to midazolam to avoid acute deterioration of minimal encephalopathy: A randomized, controlled study

Abstract: The study demonstrates that propofol sedation for upper GI endoscopy does not cause acute deterioration of minimal hepatic encephalopathy and is associated with improved recovery in patients with liver cirrhosis. Propofol should be recommended for these patients as an alternative to midazolam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
92
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 46 publications
4
92
0
2
Order By: Relevance
“…One shortcoming of this study might have been that doses of midazolam were lower than doses used in previous studies. 16,17 Nevertheless, the average dose observed in the group whose sedation was considered ineffective is consistent with the average weight observed for this group, which means that the maximum dose was achieved but without the expected results.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…One shortcoming of this study might have been that doses of midazolam were lower than doses used in previous studies. 16,17 Nevertheless, the average dose observed in the group whose sedation was considered ineffective is consistent with the average weight observed for this group, which means that the maximum dose was achieved but without the expected results.…”
Section: Discussionsupporting
confidence: 79%
“…11,17 In a cohort study, Amorós et al 11 demonstrated that deep sedation with propofol did not precipitate minimal or overt hepatic encephalopathy. This observation was confirmed by Riphaus et al 17 in a prospective, randomized study comparing propofol with midazolam for sedation in cirrhotic patients during therapeutic endoscopic procedures.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It was safe even in elderly individuals and in those with multiple co-morbid conditions [22]; however, the effect on hepatic encephalopathy was not investigated. More recently, a trial with a close design has been published by Riphaus et al [23]. However, his study differs from our study by several points including the etiology of liver disease (alcohol vs. viral), selection of the control groups (healthy individuals without sedation and without endoscopy vs. healthy individuals with sedation and with endoscopy), severity of preexisting liver disease (six patients with Child-Pugh's Class C vs. none with Child-Pugh's Class C), amount of propofol (50-320 mg vs. 70-100 mg), and finally the timing of the number connection test evaluation (2 h vs. 1 h).…”
Section: Introductionmentioning
confidence: 97%
“…Liver patients are at potentially greater risk of complications, including cardiopulmonary compromise, and possible precipitation or exacerbation of encephalopathy, including sub-clinical encephalopathy [4,5]. Recently, the negative effects of using midazolam sedation during peroral endoscopic examination, such as prolonging hepatic encephalopathy in liver cirrhosis (LC) patients, have been reported [4,6,7]. Moreover, there were some reports that the risk of hypoxemia, bradycardia and hypotension increased during moderate sedation [8,9].…”
Section: Introductionmentioning
confidence: 99%